2020
DOI: 10.3389/fendo.2020.00129
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Different Progestins in Women With Advanced Endometriosis Undergoing Controlled Ovarian Hyperstimulation for in vitro Fertilization-A Single-Center Non-inferiority Randomized Controlled Trial

Abstract: Is it possible to use different progestins cotreatment with human menopausal gonadotrophin (hMG) in women with advanced endometriosis but normal ovulation during controlled ovarian hyperstimulation (COH) in vitro fertilization (IVF)? Whether different progestins treatments can be an alternative choice for women with severe endometriosis in considering IVF/ICSI treatment remains unknown? Design: Non-inferiority randomized clinical trial. Setting: Tertiary-care academic medical center. Population: Four hundred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 31 publications
(55 reference statements)
0
19
0
Order By: Relevance
“…Previous studies reported that the IVF outcomes of patients with endometriosis were improved by pretreatment with DNG, and myo-inositol is of proven utility in those with PCOS [ 45 , 46 ]. Our centre also published some work in this field on the basis of a novel ovarian stimulation strategy named progestin primed ovarian stimulation (PPOS) [ 15 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the IVF outcomes of patients with endometriosis were improved by pretreatment with DNG, and myo-inositol is of proven utility in those with PCOS [ 45 , 46 ]. Our centre also published some work in this field on the basis of a novel ovarian stimulation strategy named progestin primed ovarian stimulation (PPOS) [ 15 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, 5,000 IU hCG (Lizhu Pharmaceutical Trading Co., Zhuhai, China) or 0.1 mg triptorelin (decapeptyl; Ferring Pharmaceuticals, Saint-Prex, Switzerland) or a combination of the two was administered to induce ovulation, depending on the preference of the doctors in charge. If a markedly elevated LH [LH>15 mIU/ml ( 12 , 13 )] occurred, namely, a spontaneous LH surge was detected, we applied trigger drugs immediately or might not have used any medications for trigger, the decision of which was also based on the preference of the doctors in charge. The IUI operation was performed within 24 h after the observed LH surge.…”
Section: Methodsmentioning
confidence: 99%
“…It has been proposed that co-administration of progestins in COS might improve the quality of the oocytes and embryos. A non-inferiority randomized controlled trial has shown the effectiveness of PPOS protocol in patients with advanced endometriosis but normal ovarian reserve ( 33 ). Moreover, neonatal outcomes and congenital malformations were comparable in PPOS protocol compared with conventional ovarian stimulation protocol in maternal endometriosis ( 34 ).…”
Section: Disscusionmentioning
confidence: 99%